Absenteeism among health professional during COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
Objective: To know through the literature the scientific production on the absenteeism of health professionals during the COVID-19 pandemic. Methods: This is an Integrative Literature Review, with a qualitative approach, carried out in the MEDLINE, LILACS, and SciELO databases Articles from January 2019 to January 2022 were selected. Results: Of the six selected articles, three thematic categories were created, namely: Impacts of the COVID-19 pandemic on health services; The use of PPE and the relationship whit absenteeism by COVID-19; Health category with the highest tendency to absenteeism. The study findings indicate know serious is the absenteeism of health professionals to institutions and patients care due to their high exposure to COVID-19. Final considerations: The planning of adequate health care is the main tool for ham reduction to professionals, institutions and patients, requiring a better health management strategy.